Hyperbaric Oxygen Therapy to Reduce Blood Glucose Level on Patients Diabetes Mellitus - Ana Zakiyah; Veni Septian Anggraini (Journal of Nursing Care, 2019)
Oxygen hyperbaric therapy is a clinical treatment by inhalation of pure oxygen (FiO2 = 100%), resulting in increasing oxygen levels in the blood and tissues. Currently, hyperbaric oxygen therapy is used for additional management in diabetes mellitus. The purpose of this study was to know the effect of hyperbaric oxygen therapy in case of diabetes mellitus to changes in blood glucose level. Type of research was pre-experimental one group pre-test post design. The population in this study was diabetes mellitus patients, so that the sample obtained 47 respondents. Patients were given 100% oxygen inhalation with a pressure of 2.4 ATA in chamber hyperbaric oxygen. Blood glucose levels were measured before and after hyperbaric oxygen therapy. Glucose levels before the average therapy were 229 mg / dl and after treatment averaged 159 mg / dL. Statistical analysis with t test showed p value 0.000 <α (0,05), so there was the influence of hyperbaric oxygen therapy with decreasing blood glucose level. There are improvements pancreatic beta cell function and increased tissue sensitivity to insulin due to increased oxidative phosphorylation process in pancreatic beta-cell mitochondria to increase ATP production in pancreatic beta cells.   Checks need to be done periodically in one period with using the time series method, so that long-term effects can be known and need to be reviewed by the last use of anti-diabetes drugs and insulin